Job Autonomy, workload, job stress and Intention to Leave on Millennial: A Literature Review - Gazali, G; Sandi, Kemal; Lestari, Yuni; Zainurrafiqi, z (International Journal of Artificial Intelligence Research, 2022)
This study aims to examine previous research to determine the effect of job autonomy and workload on the intention to leave mediated by job stress for millennial workers. This study applies various theories, namely the theory of Job Demand Resources (JDR), and Conservation of Resources (COR) to explain the relationship between variables. As a literature study article, this article contributes to developing a conceptual framework about intention to leave in the perspective of millennial workers. This article is important for management and further research considering that not many previous studies have used the theoretical framework of Job Demand Resources (JDR) and Conservation of Resources (COR) to test similar research models. This study has limitations in obtaining research that examines job autonomy, workload, job stress and intention to leave in the perspective of millennial workers. Nevertheless, this study brings up a new framework that illustrates the contribution of job autonomy, workload, and job stress to intention to leave.